THE ROLE OF THE ‘ORDINARY READER’ IN GERALD O WEST’S HERMENEUTICS - Akper, Godwin I. (Scriptura, 2005)
This essay explores the role of the "ordinary reader" in Gerald O West’s hermeneutics. Firstly, it offers a brief overview of the background context of liberation from which West developed his hermeneutics. Secondly, West’s hermeneutics of liberation in its South African context is explored. Thirdly, the role of the so-called "ordinary reader", especially in the interpretive process, in West’s hermeneutics of liberation, is examined. The essay argues that the voices of the "ordinary readers" in the collaborative reading need to be clearly evident, so that it does not seem as though the socially engaged biblical scholar is simply reading through the "ordinary readers".